Língua e sociedade: o caso do discurso de Leonel Brizola e o semantismo social nele revelado - Rocha, Gisandra Cemin da (2018)
The present work is based on the studies realized by Émile Benveniste about the language, and discuss the relation language and society, considering that all man a social and cultural being, and this is possible to verify from the moment that he enunciate, that is, when he appropriates of the languistic system and mobilizes the language in the discourse. It is from Benveniste’s axiom, the man in the language, that we conceptualize that the author calls in his work like social semantism, this one that is defined from principles benvenistianos, from the anthropology of enunciation's perspective, that is, through the relationship between man, language and culture, and is the term that generated the main theme of this study and which instigated the research here discussed. As main objective we search to analyze the social semantism present in the Leonel de Moura Brizola's discourses, from the relationship of language and society, in order to determine the way as the individuals I and you relate, from the political discourse's perspective. The theoretical basis of this study is based on relation language and society, in the anthropology of enunciation, and in the relation of interpretation, presented by Benveniste (2005, 2006), also studied by Flores (2013, 2017) and Dessons (2006). The methodological procedures used in the research consist of a qualitative, exploratory and documentary approach, because this study consists in the investigation and in search for principles and theoretical explanations about the main theme, and utilize like corpus closed documents, this is, discourses already realized and now documented in videos, books and internet's websites, which be examined with the intent of to find the social semantism in the Leonel Brizola’s discourse here analyzed. The analysis is carried out by checking the linguistic forms of the politician in question, searching for discover what factors contributed, through the language, to the fact that he had won his audience for irreverence, sincerity and irony, not using "half words", and also being oftentimes repudiated for the same reason. It is understood, from the analysis carried out, that the social semantism revealed in the Leonel Brizola's discourse is shown by the way in which he used the language’s way to reach the society that he was addressing, expressing his opinions, but at the same time, searching to emphasize certain values that were important to that society, in order to achieve success in his discourse.